Structural‐Activity Relationship‐Inspired the Discovery of Saturated Fatty Acids as Novel Colistin Enhancers - Jinju Cai; Jingru Shi; Chen Chen; Mengping He; Zhiqiang Wang; Yuan Liu (Advanced Science, 2023)
Abstract The emergence and prevalence of mobile colistin resistance gene mcr have dramatically compromised the clinical efficacy of colistin, a cyclopeptide antibiotic considered to be the last option for treating different‐to‐treat infections. The combination strategy provides a productive and cost‐effective strategy to expand the lifespan of existing antibiotics. Structural‐activity relationship analysis of polymyxins indicates that the fatty acyl chain plays an indispensable role in their antibacterial activity. Herein, it is revealed that three saturated fatty acids (SFAs), especially sodium caprate (SC), substantially potentiate the antibacterial activity of colistin against mcr‐positive bacteria. The combination of SFAs and colistin effectively inhibits biofilm formation and eliminates matured biofilms, and is capable of preventing the emergence and spread of mobile colistin resistance. Mechanistically, the addition of SFAs reduces lipopolysaccharide (LPS) modification by simultaneously promoting LPS biosynthesis and inhibiting the activity of MCR enzyme, enhance bacterial membrane damage, and impair the proton motive force‐dependent efflux pump, thereby boosting the action of colistin. In three animal models of infection by mcr‐positive pathogens, SC combined with colistin exhibit an excellent therapeutic effect. These findings indicate the therapeutic potential of SFAs as novel antibiotic adjuvants for the treatment of infections caused by multidrug‐resistant bacteria in combination with colistin.